Gas-barrier coating film forming coating composition and gas-barrier laminate

CN123022544APending Publication Date: 2026-10-30TOYO SEIKAN GRP HLDG LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202580024290.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-04-01
Filing Date
2025-03-26
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0004]上述专利文献1的复合结构体满足氧气阻隔性和水蒸气阻隔性这两方,但对于内容物所具有的酸、碱,在稳定性的方面有所担心

Benefits of technology

[0035]本发明的阻气性层叠体因金属氧化物不会凝聚而均匀地高度分散,促进了金属氧化物与磷酸化合物或硫酸化合物的反应,形成了均匀且致密的交联结构,因此非极性气体分子和极性气体分子的透过得到抑制,表现出优异的氧气阻隔性和水蒸气阻隔性。此外,阻气性涂膜中的成为极性气体(水分子)的通道的未反应的羟基量降低,因此进一步提高了水蒸气阻隔性。而且,由于金属氧化物粒子的凝聚得到抑制,因此涂膜的透明性也优异,在25μm厚的双轴拉伸聚对苯二甲酸乙二醇酯基材上形成有涂膜的层叠体的情况下,雾度小于9.0%。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application provides a gas barrier laminate having a gas barrier coating film, and a coating composition capable of efficiently forming such a gas barrier coating film, the gas barrier coating film being excellent in oxygen barrier property and transparency, and having more excellent water vapor barrier property than existing gas barrier coating films. A gas barrier laminate characterized by having a gas barrier coating film on a substrate, the coating film being free from discoloration due to an organic compound such as an amine compound, a carboxylic acid compound, a ratio (P2 / P1) of a peak area (P2) in the range of 2600 to 3700 cm-1 to a peak area (P1) in the range of 850 to 1350 cm-1 in an infrared absorption spectrum of the coating film being less than 0.772, and a content ratio (P / Zr) of Zr (Zr-Kα) to P (P-Kα) in a fluorescent X-ray measurement of the coating film being in the range of 1.39 to 2.59. ‑1 ‑1 ​​
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a coating composition for forming a gas barrier film and a gas barrier laminate having a coating film formed from the coating composition, and more specifically, to a gas barrier laminate having excellent oxygen barrier and water vapor barrier properties, as well as excellent transparency, and a coating composition capable of forming such a coating film. Background Technology

[0002] It is known in the past that gas barrier laminates are formed on plastic substrates by forming films composed of metal atoms and phosphorus atoms.

[0003] For example, Patent Document 1 describes a composite structure having a substrate (X) and a layer (Y) stacked on the substrate (X), wherein the layer (Y) contains a reaction product (R), which is a reaction product formed by reacting a metal oxide (A) with a phosphorus compound (B) at a depth of 800–1400 cm⁻¹. -1 In the infrared absorption spectrum of the layer (Y) within the range of [value], infrared absorption becomes the largest end number (n). 1 ) in 1080~1130cm -1 Within the range, the metal atoms (M) constituting the metal oxide (A) are aluminum.

[0004] The composite structure in Patent Document 1 satisfies both oxygen and water vapor barrier properties, but there are concerns about its stability in the presence of acids and alkalis in the contents. Furthermore, during the drying process of the film-forming process, volatile acids contained in the coating evaporate, posing a technical challenge of low productivity.

[0005] The inventors have proposed a coating composition in which the composite structure formed by the reaction products of metal oxides and phosphoric acid compounds solves the above-mentioned problems, and by containing specific additives, it can exhibit superior oxygen barrier and water vapor barrier properties (Patent Document 2).

[0006] In the coating composition for forming a gas barrier coating film described in Patent Document 2, an amine compound containing polyvalent metal ions and organic carboxylic acids is used as a specific additive. The polyvalent metal ions supplement the metal ions, and the amine compound reacts with the metal ions, carboxylic acid, and phosphoric acid to be introduced into the cross-linked structure, acting as a binder between metal oxide particles. Therefore, a defect-free coating film can be formed, exhibiting superior oxygen barrier and water vapor barrier properties.

[0007] Furthermore, the inventors have proposed a coating composition that, as a further improvement on the coating composition of Patent Document 2, contains at least one of a metal alkoxide, a hydrolysate of a metal alkoxide, and a metal hydroxide, together with a metal oxide and a phosphoric acid compound.

[0008] Existing technical documents

[0009] Patent documents

[0010] Patent Document 1: Japanese Patent No. 4961054

[0011] Patent Document 2: International Publication 2022 / 075352 Summary of the Invention

[0012] The problem that the invention aims to solve

[0013] The coating film formed by the above-mentioned coating composition can efficiently form a coating film with excellent oxygen barrier and water vapor barrier properties due to the uniform and dense cross-linked structure of metal oxides and phosphoric acid compounds, as well as excellent transparency without yellowing due to the reaction of amine compounds and carboxylic acids. However, through further repeated studies, the inventors have found that the water vapor barrier properties can be further improved in the coating film formed by the above-mentioned coating composition.

[0014] Therefore, the object of the present invention is to provide a gas barrier laminate having excellent oxygen barrier properties and transparency, and having superior water vapor barrier properties compared to existing gas barrier coatings, and a coating composition capable of efficiently forming such a gas barrier coating.

[0015] Solution for solving the problem

[0016] According to the present invention, a gas barrier laminate is provided, characterized in that it is a gas barrier laminate having a gas barrier coating film on a substrate, wherein the coating film is formed by a reaction product obtained by reacting a metal alkoxide, a hydrolysate of a metal alkoxide, a metal hydroxide, a zirconium oxide, and a phosphoric acid compound or a sulfuric acid compound, wherein the ratio of Zr (Zr-Kα) to P (P-Kα) in the fluorescence X-ray diffraction of the coating film (P / Zr) is in the range of 1.39 to 2.59, and the infrared absorption spectrum of the coating film is in the range of 2600 to 3700 cm⁻¹. -1 The peak area (P2) is 850–1350 cm⁻¹ -1 The ratio of peak area (P1) to peak area (P2 / P1) is less than 0.772.

[0017] In the gas-barrier laminate of the present invention, the preferred embodiment is:

[0018] [1] A biaxially stretched polyethylene terephthalate film with a thickness of 25 μm was used as a substrate, and a coating with a coating weight of 1.8–2.2 g / m was formed on the substrate. 2 The haze of the gas barrier laminate of the coating is less than 9.0%;

[0019] [2] The metal alkoxide, the hydrolysate of the metal alkoxide, and the metal hydroxide are aluminum, and the ratio of Zr (Zr-Kα) to Al (Al-Kα) in the fluorescence X-ray determination of the coating film (Al / Zr) is in the range of 0.15 to 0.58.

[0020] [3] The coating film has an infrared absorption spectrum of 1000–1120 cm⁻¹ -1 The infrared absorption peak is the largest within the range of [instrument name missing].

[0021] [4] A biaxially stretched polyethylene terephthalate film with a thickness of 25 μm was used as the substrate, and the coating amount formed on the substrate was 1.8–2.2 g / m. 2 The water vapor permeability of the gas barrier laminate formed by further laminating a biaxially stretched polyethylene terephthalate film with a thickness of 25 μm on the coating film and an adhesive layer between the coating film and the coating film is less than 0.100 g / m². 2 · Day (40℃ 90%RH).

[0022] According to the present invention, a substrate for vapor deposition comprising the above-described gas barrier laminate is also provided.

[0023] According to the present invention, a coating composition for forming a gas barrier coating film is also provided, characterized in that the coating composition for forming a gas barrier coating film contains at least one of a metal alkoxide, a hydrolysate of a metal alkoxide, a metal hydroxide, a metal oxide, and a phosphoric acid compound or a sulfuric acid compound, wherein when the coating composition for forming a gas barrier coating film is prepared into a water / isopropanol (60 / 40) dispersion with a solid content of 5-7% by mass, the viscosity ratio (A / B) of the dispersion, measured using a Brookfield viscometer at a temperature of 25°C and a spindle speed of 50 rpm, is less than 3.6.

[0024] In the coating composition for forming a gas barrier coating film of the present invention, the preferred option is:

[0025] [1] When the coating composition for forming a barrier coating film is prepared into a water / isopropanol (60 / 40) dispersion with a solid content of 5 to 7% by mass, the viscosity of the dispersion, measured by a Brookfield viscometer at a temperature of 25°C and a spindle speed of 50 rpm, is less than 113.9 mPa·sec.

[0026] [2] The metal species of the metal alkoxide or metal hydroxide is at least one of aluminum, titanium, iron, and zirconium;

[0027] [3] The metal alkoxide is at least one of methanol, ethanol, propoxide, isopropoxide, butoxide, isobutoxide, sec-butoxide, and tert-butoxide;

[0028] [4] The metal alkoxide is aluminum isopropoxide;

[0029] [5] The metal hydroxide is aluminum hydroxide;

[0030] [6] The metal oxide is zirconium oxide or aluminum oxide;

[0031] [7] The metal oxide is a crystalline zirconium oxide;

[0032] [8] The phosphoric acid compound is at least one of orthophosphoric acid, metaphosphoric acid, polyphosphoric acid, and cyclic polyphosphoric acid.

[0033] Furthermore, according to the present invention, a method for manufacturing a coating composition for forming a gas barrier coating film is also provided, characterized in that the method for manufacturing the coating composition for forming a gas barrier coating film is the same as the method for manufacturing the coating composition for forming a gas barrier coating film described above, wherein at least one of a metal alkoxide, a hydrolysate of a metal alkoxide, a metal hydroxide, a metal oxide, and a phosphoric acid compound or a sulfuric acid compound is mixed and stirred such that the viscosity, measured using a Brookfield viscometer at a temperature of 25°C and a spindle speed of 50 rpm, is less than 113.9 mPa·sec.

[0034] Invention Effects

[0035] The gas-barrier laminate of this invention exhibits excellent oxygen and water vapor barrier properties because the metal oxides are uniformly and highly dispersed without agglomeration. This promotes the reaction between the metal oxides and phosphoric acid or sulfuric acid compounds, forming a uniform and dense cross-linked structure. Consequently, the permeation of both non-polar and polar gas molecules is suppressed. Furthermore, the amount of unreacted hydroxyl groups in the gas-barrier coating that act as channels for polar gases (water molecules) is reduced, further enhancing water vapor barrier properties. Moreover, due to the suppression of metal oxide particle agglomeration, the coating also exhibits excellent transparency; in the case of a laminate with the coating formed on a 25 μm thick biaxially stretched polyethylene terephthalate substrate, the haze is less than 9.0%.

[0036] In the coating composition for forming a gas barrier film of the present invention, the thixotropy is reduced because the metal oxide particles are uniformly and highly dispersed without agglomeration. Therefore, compared with conventional coating compositions for forming gas barrier films, the viscosity is adjusted to be lower, resulting in excellent coatability and leveling properties, and a uniform and smooth coating film can be formed. Furthermore, due to the excellent smoothness of the coating film, light scattering on the coating surface is suppressed, and the absence of metal oxide particle agglomeration leads to reduced haze and excellent transparency. Moreover, due to the excellent coatability, the generation of coating defects is reduced. As described above, the highly dispersed metal oxide particles form a uniform and dense cross-linked structure, which in turn leads to a coating film with excellent oxygen and water vapor barrier properties. Furthermore, since the coating does not contain volatile acids, no countermeasures are required during the drying process, resulting in excellent productivity and safety. Attached Figure Description

[0037] Figure 1 This is a cross-sectional view showing an example of the gas barrier laminate of the present invention.

[0038] Figure 2 This is a cross-sectional view showing another example of the gas barrier laminate of the present invention. Detailed Implementation

[0039] (Gas barrier laminate)

[0040] The key features of the gas barrier coating formed on the substrate in the gas barrier laminate of the present invention are as follows: In the infrared absorption spectrum from 2600 to 3700 cm⁻¹ -1 The peak area (P2) is 850–1350 cm⁻¹ -1 The ratio of peak area (P1) to peak area (P2 / P1) is less than 0.772.

[0041] The gas barrier coating in the gas barrier laminate of the present invention can be formed from a coating composition for forming a gas barrier coating, which contains at least one of metal alkoxides, hydrolysates of metal alkoxides, and metal hydroxides together with metal oxides and phosphoric acid compounds, as described later. Specifically, it is a coating composition in which the metal oxide is zirconium oxide. In particular, it is a coating formed by crosslinking metal oxides with phosphoric acid compounds or sulfuric acid compounds to form metal phosphate salts or metal sulfate salts. Furthermore, metal alkoxides, etc., are also introduced into the aforementioned crosslinked structure by reacting with phosphoric acid compounds or sulfuric acid compounds to form metal phosphate salts or metal sulfate salts, functioning as a binder between metal oxide particles.

[0042] The peak area (P1) in the infrared absorption spectrum is the peak area of ​​the metal phosphate salt or metal sulfate salt in the FT-IR measurement of the coating on the substrate. On the other hand, the peak area (P2) is the peak area of ​​the hydroxyl group of the coating monomer. The ratio (P2 / P1) is less than 0.772, which means that the reaction of metal oxides and phosphoric acid compounds is promoted efficiently as described above, a dense cross-linked structure without defects caused by the formation of metal phosphate salts is formed efficiently, and unreacted hydroxyl groups are reduced.

[0043] Furthermore, in the gas-barrier laminate of the present invention, as described above, due to the excellent dispersibility of zirconium oxide (hereinafter, sometimes referred to as "metal oxide") in the coating film, the zirconium oxide particles (hereinafter, sometimes referred to as "metal oxide particles") do not aggregate, thus improving the transparency of the coating film, and forming a 1.8 to 2.2 g / m² coating on a biaxially stretched polyethylene terephthalate film with a thickness of 25 μm. 2 In the case of a gas barrier laminate with a certain coating amount, the haze is less than 9.0%.

[0044] In the case where zirconium oxide is used as the metal oxide, phosphoric acid is used as the phosphoric acid compound, or aluminum isopropoxide or aluminum hydroxide is used as the metal alkoxide, the content ratio (Al / Zr) of Zr (Zr-Kα) obtained by fluorescence X-ray determination of zirconium oxide to Al (Al-Kα) obtained by fluorescence X-ray determination of aluminum alkoxide is preferably in the range of 0.15 or more and less than 0.60, particularly preferably in the range of 0.33 to 0.58, and even more preferably in the range of 0.43 to 0.58.

[0045] By keeping the above-mentioned content ratio (Al / Zr) within the above-mentioned range, the dense cross-linked structure formed by zirconium oxide and phosphoric acid compound is not damaged, and the above-mentioned effects brought about by aluminum alkoxide and the like can be exhibited, and excellent oxygen barrier and water vapor barrier properties can be exhibited.

[0046] Furthermore, when using zirconium oxide as the metal oxide, phosphoric acid as the phosphoric acid compound, or aluminum isopropoxide or aluminum hydroxide as the metal alkoxide, the ratio (P / Zr) of Zr (Zr-Kα) obtained by fluorescence X-ray determination of zirconium oxide to P (P-Kα) obtained by fluorescence X-ray determination of phosphoric acid compound is preferably in the range of 1.39 or more and less than 2.68, particularly preferably in the range of 1.49 to 2.59, and even more preferably in the range of 1.91 to 2.59.

[0047] By ensuring the P / Zr ratio is within the specified range, the phosphate compound reacts efficiently with the metal oxide in the coating film without excess or deficiency, resulting in a uniform and dense film exhibiting excellent oxygen and water vapor barrier properties. Conversely, if the P / Zr ratio, as determined by X-ray fluorescence, is less than the specified range and the phosphate compound is insufficient, the bonding between metal oxide particles is inadequate, leading to defects in the coating structure and potentially reducing oxygen and water vapor barrier properties. On the other hand, if the P / Zr ratio, as determined by X-ray fluorescence, is greater than the specified range and the phosphate compound is excessive, the amount of hydroxyl groups derived from the phosphate groups increases, and oxygen and water vapor barrier properties may still decrease.

[0048] The coating in the gas barrier laminate of the present invention preferably has an infrared absorption spectrum in the range of 1000–1120 cm⁻¹ on the substrate. -1 The infrared absorption peak is largest within the range described above. That is, as described above, the coating in the barrier laminate of the present invention efficiently forms a cross-linked structure based on the formation of metal phosphate salts due to the excellent dispersibility of the metal oxides. Therefore, it exhibits the largest absorption peak within the aforementioned range derived from metal phosphate salts.

[0049] Regarding the gas barrier laminate of the present invention, as described above, the surface of unreacted metal oxide particles and hydroxyl groups derived from phosphoric acid compounds in the coating film are reduced, and the permeation of nonpolar gas molecules and polar gas molecules is suppressed by its uniform and dense structure. Therefore, it has excellent oxygen barrier and water vapor barrier properties, especially excellent water vapor barrier properties.

[0050] Furthermore, the gas molecules that can suppress permeation, other than oxygen and water vapor, are not limited to these; examples include hydrogen, helium, nitrogen, methane, ammonia, and acidic gases such as hydrogen chloride, hydrogen sulfide, carbon dioxide, sulfur oxides, and nitrogen oxides.

[0051] For example, if a 25 μm thick biaxially stretched polyethylene terephthalate film is used as the substrate, a coating with a coverage of 1.8–2.2 g / m² can be formed on this substrate. 2 The water vapor permeability of the gas barrier laminate, which forms a 25 μm thick biaxially stretched polyethylene terephthalate film through an adhesive layer, is less than 0.100 g / m³. 2 • At 40℃ and 90%RH, it has excellent water vapor barrier properties.

[0052] Furthermore, if a 25 μm thick biaxially stretched polyethylene terephthalate film is used as the substrate, a coating with a thickness of 1.8–2.2 g / m² can be formed on this substrate. 2The oxygen permeability of the gas barrier laminate, which forms a 25μm thick biaxially stretched polyethylene terephthalate film through an adhesive layer, is 25cc / m. 2 It has excellent oxygen barrier properties when the temperature is below 40℃ and 90%RH.

[0053] Furthermore, as described above, the gas-barrier laminate of the present invention forms a gas-barrier coating film in a state where the metal oxide particles are uniformly and highly dispersed without agglomeration, thereby forming a uniform and smooth coating film with excellent optical properties and a haze of less than 9.0%. In addition, a coating with a coating weight of 1.8 to 2.2 g / m is formed on a 25 μm thick biaxially stretched polyethylene terephthalate film as a substrate. 2 In the gas barrier laminate of the coating, the total light transmittance is above 80%, and in addition, if the gloss at an angle of 60° is above 100, it has excellent optical properties.

[0054] The gas-barrier laminate of the present invention is a laminate formed by forming a gas-barrier layer of the above-described gas-barrier coating on at least one surface of a substrate. Preferably, as shown in the figure... Figure 1 As shown, a gas barrier layer 3 is formed on the substrate 1 through the tackifying coating 2 described later. The tackifying coating 2 is a coating film with excellent adhesion to the substrate 1. By forming a gas barrier layer on this coating film, the interlayer adhesion between the gas barrier layer and the plastic substrate is significantly improved, inhibiting delamination in high temperature or high humidity environments. Furthermore, even when sterilization by boiling is performed, the gas barrier layer can be effectively prevented from peeling off from the substrate.

[0055] Furthermore, in the gas-barrier laminate of the present invention, such as Figure 2 As shown, preferably, a resin layer 5 made of thermoplastic resin is formed on the gas barrier layer 3 with an adhesive layer 4 in between.

[0056] [Base material]

[0057] As the substrate for the gas barrier laminate of the present invention, conventionally known substrates composed of resins such as thermoplastic resins and thermosetting resins, or fibers such as paper and nonwoven fabrics can be used. However, it is preferred that any packaging material and molded structure, such as film, sheet, bottle, cup, plate, or can, made of thermoformable thermoplastic resin by methods such as extrusion molding, biaxial stretch film molding, cast film molding, injection molding, blow molding, stretch blow molding, or pressure molding can be used.

[0058] Examples of thermoplastic resins constituting the base material include: low-, medium-, or high-density polyethylene, linear low-density polyethylene, polypropylene, ethylene-propylene copolymer, ethylene-1-butene copolymer, ionomer, ethylene-vinyl acetate copolymer, ethylene-vinyl alcohol copolymer, and other olefin copolymers; polyesters such as polyethylene terephthalate, polybutylene terephthalate, polyethylene terephthalate / ethylene isophthalate, and polyethylene naphthalate; polyamides such as nylon 6, nylon 6,6, nylon 6,10, and adipamide; polyimides such as diamine-carboxylic anhydride copolymers; styrene copolymers such as polystyrene, styrene-butadiene block copolymers, styrene-acrylonitrile copolymers, and styrene-butadiene-acrylonitrile copolymers (ABS resin); vinyl chloride copolymers such as polyvinyl chloride and vinyl chloride-vinyl acetate copolymers; acrylic copolymers such as polymethyl methacrylate and methyl methacrylate / ethyl acrylate copolymers; and polycarbonate, etc.

[0059] In addition, from the perspective of environmental response in recent years, chemically recycled polyethylene terephthalate, mechanically recycled polyethylene terephthalate, biomass-derived polyethylene terephthalate, biomass-derived olefins, and recycled olefins can be used.

[0060] In this invention, sheets formed of polyethylene terephthalate, polybutylene terephthalate or polypropylene are particularly preferred.

[0061] These thermoplastic resins can be used alone or in blends of two or more, and different resins can exist in laminates. Furthermore, the plastic substrate can be a single layer or a laminate of two or more layers, obtained, for example, through simultaneous melt extrusion or other lamination processes. Additionally, from the viewpoint of improving heat resistance, the plastic material can undergo uniaxial or biaxial tensile processing to enhance strength.

[0062] In the thermoformable thermoplastic resin, one or more additives such as pigments, antioxidants, antistatic agents, ultraviolet absorbers, and lubricants may be added, depending on the desired amount, in the range of 0.001 to 5.0 parts by weight relative to 100 parts by weight of the resin.

[0063] Furthermore, for example, to strengthen the container, one or more of the following can be added in an amount of 2 to 150 parts by weight relative to 100 parts by weight of the thermoplastic resin: fiber reinforcing materials such as glass fiber, aromatic polyamide fiber, carbon fiber, pulp, cotton / cotton lint, powder reinforcing materials such as carbon black, silica, or sheet reinforcing materials such as glass sheets or aluminum sheets. Moreover, for the purpose of increasing the volume, one or more of the following can be added in an amount of 5 to 100 parts by weight relative to 100 parts by weight of the thermoplastic resin: heavy or soft calcium carbonate, mica, talc, kaolin, gypsum, clay, barium sulfate, alumina powder, silica powder, magnesium carbonate, etc., according to its own known formulation.

[0064] Furthermore, to improve gas barrier properties, flaky inorganic powders, such as water-swellable mica and clay, can be added in an amount of 5 to 100 parts by weight relative to 100 parts by weight of the thermoplastic resin, according to its known formulation.

[0065] Similarly, to improve gas barrier properties, thin film layers of inorganic materials such as silicon oxide and aluminum oxide can be physically or chemically deposited on plastic substrates using vapor phase evaporation.

[0066] Furthermore, the substrate can ultimately be a film, sheet, or a molded product such as a container, or the coating can be pre-applied to a preform used for molding into a container. Examples of such preforms include: bottomed or bottomless cylindrical preforms for biaxial stretch blow molding; tubes for molding plastic containers; sheets for vacuum forming, pneumatic forming, plug-assist forming; or films for heat-sealing caps and bag making.

[0067] [Adhesion-promoting coating layer]

[0068] As a tackifying coating to be formed on the surface of a substrate as needed, a tackifying coating conventionally formed in gas-barrier laminates can be formed. Preferably, a tackifying coating formed from a conventionally known polyurethane resin, composed of a hydroxyl-containing compound as the main agent (such as an acrylic resin or polyol) and an isocyanate-based curing agent, or a tackifying coating further incorporating a silane coupling agent, or a tackifying coating formed from a resin containing hydrophilic groups and a silane coupling agent, will be described later.

[0069] (Base material for vapor deposition)

[0070] As described above, the gas barrier laminate of the present invention has excellent gas barrier properties, especially excellent water vapor barrier properties, and is therefore preferably used as a substrate for forming vapor-deposited films.

[0071] There are no particular limitations on the method for forming the vapor-deposited film on the substrate. It can be formed by physical vapor deposition such as sputtering, vacuum vapor deposition, and ion plating, or by chemical vapor deposition such as plasma CVD. Furthermore, the vapor-deposited film formed is not limited to these methods, and examples include gold, silver, copper, titanium, nickel, aluminum, silicon oxide, titanium oxide, aluminum oxide, a mixture of silicon dioxide and aluminum oxide, indium tin oxide, and diamond-like carbon.

[0072] (Coating composition for forming gas barrier coating film)

[0073] The important features of the coating composition for forming a gas barrier coating film capable of forming a gas barrier laminate of the present invention are as follows: the coating composition for forming a gas barrier coating film is a coating composition for forming a gas barrier coating film containing at least one of a metal alkoxide, a hydrolysate of a metal alkoxide, a metal hydroxide, a metal oxide, and a phosphoric acid compound or a sulfuric acid compound, wherein, when the coating composition for forming a gas barrier coating film is prepared into a water / isopropanol (60 / 40) dispersion with a solid content of 5-7% by mass, the viscosity ratio (A / B) of the dispersion, measured using a Brookfield viscometer at a temperature of 25°C and a spindle speed of 50 rpm, is less than 3.6.

[0074] That is, generally speaking, coating compositions exhibit thixotropy. Since this thixotropy depends on shear stress during dispersion, the viscosity decreases when the rotation speed is high and high shear stress is applied, and increases when the rotation speed is low and shear stress is weak. The coating composition for forming a barrier coating film of the present invention has the following characteristics: due to the high dispersion of metal alkoxides, metal oxides, and phosphoric acid compounds in the coating composition, the thixotropy is reduced. Therefore, as described above, it has a low viscosity even at a low rotation speed (50 rpm), and the viscosity ratio (A / B) is less than 3.6.

[0075] In the coating composition for forming a gas barrier coating film of the present invention, when the coating composition for forming a gas barrier coating film is prepared as a water / isopropanol (60 / 40) dispersion with a solid content of 5 to 7% by mass, the viscosity of the dispersion, measured using a Brookfield viscometer at a temperature of 25°C and a spindle speed of 50 rpm, is preferably less than 113.9 mPa·sec, and particularly preferably 26.2 to 96.0 mPa·sec. As a result, metal oxide particles and the like in the coating composition for forming a gas barrier coating film do not agglomerate but are uniformly dispersed, and a coating film exhibiting excellent oxygen barrier and water vapor barrier properties can be formed. Furthermore, as described above, it exhibits excellent coatability and leveling properties, and a defect-free coating film can be formed; in this respect, it also exhibits excellent oxygen barrier and water vapor barrier properties.

[0076] As described above, in the coating composition for forming a gas barrier film of the present invention, by containing at least one of metal alkoxide, hydrolysate of metal alkoxide, or metal hydroxide together with metal oxide, phosphoric acid compound, or sulfuric acid compound, a uniform and dense cross-linked structure is formed by metal oxide and phosphoric acid compound, etc., and by reacting metal alkoxide and the like with phosphoric acid compound, etc., it is introduced into the above cross-linked structure, and acts as a binder between metal oxide particles, thus exhibiting excellent oxygen barrier and water vapor barrier properties.

[0077] Furthermore, the reactions of metal alkoxides and their hydrolysates, as well as metal hydroxides and phosphate compounds, do not produce yellowing, thus enabling the formation of a colorless and transparent gas-barrier coating. Moreover, compared to conventional coatings containing amine compounds and carboxylic acids, it can be formed at low temperatures and in a short time, resulting in superior productivity.

[0078] [Metal oxide]

[0079] The metal oxide used in the coating composition for forming a barrier coating film according to the present invention is preferably an oxide of a metal atom with a valence of two or more, but is not limited thereto. Examples include oxides of magnesium, calcium, iron, zinc, aluminum, silicon, titanium, zirconium, etc., among which zirconium oxide is preferred.

[0080] The metal oxides used in this specification contain structures represented by MOM as their main components. M represents a metal atom, and O represents an oxygen atom.

[0081] Furthermore, zirconium oxide contains Zr and O as constituent elements. Amorphous zirconium oxide contains zirconium hydroxide (Zr(OH)4) and / or zirconium oxyhydroxide (ZrO(OH)2) as major components, while crystalline zirconium oxide contains hydrated zirconium oxide (ZrO2·xH2O) and / or zirconium oxide (ZrO2) as major components. It should be noted that "major components" refers to components present in a proportion of 50% or more. The crystallinity of zirconium oxide and zirconium oxide coated with a gas barrier can be evaluated by identifying the characteristic X-ray peaks of crystalline zirconium using conventionally known X-ray structure diffraction equipment.

[0082] In this invention, any zirconium oxide (zirconia) of crystalline or amorphous form can be used, but from the viewpoint of efficiently suppressing the permeation of gas molecules, crystalline zirconium oxide is particularly preferred.

[0083] In coatings, zirconium oxide is used in a sol containing zirconium oxide particles as the dispersion medium and inorganic acids such as nitric acid as stabilizers. However, in this invention, in order to prevent the volatilization of acids during film formation due to the presence of inorganic acids, it is preferable to use a zirconium oxide sol instead of inorganic acids such as nitric acid. This zirconium oxide sol uses carbonates, ammonium carbonates, organic dispersants, etc., and does not substantially contain volatile acids.

[0084] Furthermore, as an adhesive component, since it contains at least one of a metal alkoxide, a hydrolysate of a metal alkoxide, or a metal hydroxide that can provide a large amount of hydroxyl groups for reaction with phosphoric acid compounds, it can, in the same way as the case where amorphous zirconium oxide is used, possess both oxygen barrier and water vapor barrier properties equivalent to the case where amorphous zirconium oxide with more hydroxyl groups is used.

[0085] Furthermore, ideally, the average particle size (D50) of the primary particles of zirconium oxide is 100 nm or less, preferably 50 nm or less, and more preferably 30 nm or less, thereby forming a uniform coating with excellent transparency. It should be noted that the average particle size (D50) is the volume average particle size determined by laser diffraction / scattering, and D50 is the value representing 50% of the particle size distribution on a volume basis. Using such particulate zirconium oxide as a raw material results in excellent transparency.

[0086] Furthermore, by using the aforementioned zirconium oxide particles, a uniform and smooth coating film can be formed. Zirconium oxide has a high refractive index, and therefore can be used as a refractive index adjustment layer.

[0087] [Phosphoric acid compound]

[0088] Examples of phosphoric acid compounds used in this invention include: orthophosphoric acid, metaphosphoric acid, polyphosphoric acid, cyclic polyphosphoric acid, phosphorous acid, phosphonic acid, and their derivatives. Specific examples of polyphosphoric acid include: pyrophosphoric acid, triphosphoric acid, and polyphosphoric acid formed by the condensation of four or more phosphoric acids. Examples of the above derivatives include: orthophosphoric acid, metaphosphoric acid, polyphosphoric acid, phosphorous acid, phosphonic acid, their salts, (partially) ester compounds, halides (chlorides, etc.), and dehydrated products (phosphorus pentoxide, etc.). Furthermore, examples of phosphonic acid derivatives include compounds in which the hydrogen atom directly bonded to the phosphorus atom of phosphonic acid (HP(=O)(OH)2) is optionally substituted with an alkyl group having various functional groups (e.g., methylaminotris(methylenephosphonic acid), N,N,N',N'-ethylenediaminetetra(methylenephosphonic acid) etc.), their salts, (partially) ester compounds, halides, and dehydrated products. Moreover, phosphorylated starch and other organic polymers having phosphorus atoms can also be used. These phosphoric acid compounds can be used alone or in combination of two or more.

[0089] In this invention, at least one of orthophosphoric acid, metaphosphoric acid, polyphosphoric acid, and cyclic polyphosphoric acid is particularly preferred.

[0090] [Sulfuric acid compound]

[0091] In this invention, examples of sulfuric acid compounds that can react with metal oxides to form a dense coating, instead of the aforementioned phosphoric acid compounds, include compounds selected from the group consisting of sulfuric acid, sulfates, sulfate esters, alkyl sulfuric acid, polyoxyethylene alkyl ether sulfuric acid, and their salts. These sulfuric acid compounds can be used alone or in combination of two or more.

[0092] Sulfuric acid is particularly preferred to be used in this invention.

[0093] [Metal alkoxide or hydrolyzate thereof]

[0094] Metal alkoxides are usually represented by the following formula (1).

[0095] M n+ (OR) n- ...(1)

[0096] In the formula, R represents an organic group with 1 to 8 carbon atoms, M represents a metal atom, and n represents an integer greater than 1.

[0097] In this invention, in the above formula (1), the metal atom M is preferably any one of aluminum, titanium, iron, and zirconium, and is particularly preferably aluminum.

[0098] Furthermore, in the above formula (1), the organic group R is preferably any one of methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, and tert-butyl.

[0099] In this invention, as described above, the metal alkoxide is preferably at least one selected from methanol, ethanol, propanol, isopropanol, butanol, isobutanol, sec-butanol, and tert-butanol, wherein aluminum isopropoxide may be preferred.

[0100] [Metal hydroxide]

[0101] Metal hydroxides are usually represented by the following formula (2).

[0102] M n+ (OH) n- ...(2)

[0103] In the formula, H represents a hydrogen atom, M represents a metal atom, and n represents an integer greater than or equal to 1.

[0104] The preferred metal hydroxide is a hydroxide of any one of the metal alkoxides, such as aluminum, titanium, iron, and zirconium, with aluminum hydroxide being a preferred choice.

[0105] (Method for producing coating composition for forming gas barrier coating film)

[0106] The coating composition for forming a barrier coating film of the present invention can be any composition in the aqueous or solvent system as long as it contains the above-mentioned metal oxides, phosphoric acid compounds, and metal alkoxides, and is preferably an aqueous composition.

[0107] Ideally, in coating compositions for forming gas-barrier coatings, a sol with metal oxide microparticles as the dispersion phase is used as the aforementioned metal oxide. Furthermore, as the sol with metal oxide microparticles as the dispersion phase, it is preferable to use a sol that does not contain volatile acids as stabilizers in order to suppress adverse effects on equipment and the working environment caused by acid generation.

[0108] For the reasons stated above, ideally, volatile acids such as nitric acid, hydrochloric acid, acetic acid, and trifluoroacetic acid should not be used as anti-flocculators. These volatile acids are intended to produce dispersions with excellent transparency and viscosity stability.

[0109] The coating composition for forming a barrier coating film in this invention is prepared by mixing the aforementioned metal oxides, phosphoric acid compounds, and metal alkoxides in a solvent capable of dissolving the phosphoric acid compounds and metal alkoxides.

[0110] As such an aqueous medium, conventionally known aqueous solvents such as distilled water, deionized water, and pure water can be used. Similar to conventional aqueous compositions, it can contain organic solvents such as alcohols, polyols, their derivatives, and ketones. When using such a co-solvent, the content of the aqueous solvent in the aqueous composition can be 1 to 90% by weight. By containing solvent within the above range, the film-forming performance is improved. As such an organic solvent, amphiphilic organic solvents are preferred, and examples include: methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, sec-butanol, tert-butanol, butyl cellosolve, propylene glycol monopropyl ether, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monobutyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monobutyl ether, tripropylene glycol monomethyl ether, 3-methyl-3-methoxybutanol, acetone, methyl ethyl ketone, etc.

[0111] In the method for manufacturing the coating composition for forming a barrier coating film according to the present invention, it is important that the metal oxides, phosphoric acid compounds, etc., are uniformly and highly dispersed without agglomeration after being mixed in a solvent; therefore, a dispersion treatment is preferably performed. In the dispersion treatment, stirring is carried out such that the viscosity, measured using a Brookfield viscometer at a temperature of 25°C and a spindle speed of 50 rpm, is less than 113.9 mPa·sec, particularly in the range of 26.2 to 96.0 mPa·sec.

[0112] As a method of dispersion treatment, any conventionally known dispersion treatment can be used as long as the viscosity can be adjusted to the above-mentioned level. It is not limited to this method. The following methods can be used: pulverization treatment of cavitation particles using an ultrasonic homogenizer, mechanical dispersion treatment using a disperser using a rotating blade, dispersion using a grinder using glass or zirconia beads, etc. However, the use of an ultrasonic homogenizer is particularly preferred.

[0113] In the coating composition for forming a gas barrier coating of the present invention, phosphate compounds and metal alkoxides can be added, relative to metal oxides, within a range that does not impair oxygen barrier and water vapor barrier properties.

[0114] The amount of phosphoric acid compounds added varies depending on the type of phosphoric acid compound used and cannot be specified in general. However, when zirconium oxide is used as a metal oxide, phosphoric acid is used as a phosphoric acid compound, or aluminum isopropoxide is used as a metal alkoxide, the amount of phosphoric acid added is preferably 53.5 to 90.9 parts by mass, and particularly preferably 69.5 to 90.9 parts by mass, relative to 100 parts by mass of solid zirconium oxide, based on the non-volatile components of phosphoric acid.

[0115] Furthermore, the amount of metal alkoxides added varies depending on the type of metal alkoxide used and cannot be specified in general. However, when zirconium oxide is used as the metal oxide, phosphoric acid is used as the phosphoric acid compound, or aluminum isopropoxide is used as the metal alkoxide, aluminum isopropoxide is preferably added in an amount of 44.7 to 76.0 parts by mass, particularly 58.1 to 76.0 parts by mass, relative to 100 parts by mass of the solid content of zirconium oxide.

[0116] In the coating composition for forming a gas barrier coating of the present invention, by keeping the contents of the phosphate compound and metal alkoxide, which are binder components, within the above-mentioned range, a suitable coating composition that can form a coating with excellent transparency and gas barrier properties can be adjusted.

[0117] In the coating composition for forming a gas barrier coating of the present invention, it is ideal that the content of binder components such as phosphate compounds and metal alkoxides is within the above-mentioned range, but even within the above-mentioned range, setting the content to a higher level can reduce the viscosity of the coating composition, and is therefore particularly ideal.

[0118] Therefore, in the coating composition for forming a gas barrier coating of the present invention, by employing the above-mentioned high dispersion treatment or an increase in the binder component, or both, a coating composition having the desired viscosity characteristics can be appropriately prepared.

[0119] Furthermore, by increasing the content of phosphate compounds and metal alkoxides, the cross-linking structure formed in the coating film increases, and the cross-linking structure of the metal alkoxides, which act as binders between metal compound particles, and the reactants of phosphate compounds, namely metal phosphate salts, also increases. Therefore, a coating composition capable of forming a defect-free coating film can be provided. It should be noted that even if the content of phosphate compounds and metal alkoxides is higher than the above range, not only will no further effect be obtained, but the barrier structure of the coating film may also be defective compared to the case within the above range.

[0120] Furthermore, the coating composition for forming a barrier coating film according to the present invention preferably contains a catalyst that promotes the reaction between the metal oxide or metal alkoxide used and the phosphoric acid compound. This promotes the crosslinking reaction of the coating composition and reduces the heating temperature and heating time required to form the coating film.

[0121] Examples of such catalysts include acid catalysts such as p-toluenesulfonic acid, dodecylbenzenesulfonic acid, dinonylnaphthalenesulfonic acid, dinonylnaphthalenedisulfonic acid, cumenesulphonic acid, or amine neutralizations of these acids, with p-toluenesulfonic acid being preferred.

[0122] The acid catalyst is preferably contained in an amount of 0.1 to 10 parts by mass, and particularly preferably 1 to 3 parts by mass, relative to 100 parts by mass of the solid component of zirconium oxide.

[0123] In addition to the components mentioned above, the coating composition for forming a gas barrier film may also contain crosslinking agents, metal complexes, condensation accelerators, polymers, fillers, plasticizers, antioxidants, ultraviolet absorbers, flame retardants, defoamers, colorants, etc.

[0124] (Method for producing gas barrier laminate)

[0125] In the method for manufacturing the gas barrier laminate of the present invention, the coating composition for forming the gas barrier film of the present invention may be directly applied to at least one surface of the substrate described above, but it is preferable to apply the tackifying coating composition described later before applying the coating composition for forming the gas barrier film.

[0126] The coating amount of the tackifying coating composition is determined based on the content of polyurethane resin or carboxyl-containing polyester resin and silane coupling agent in the composition, and cannot be specified in general terms. It is preferably 0.05 to 1.00 g / m² based on the weight of the solid components of the coating film. 2 A particularly preferred formulation has a solid content of 0.10–0.50 g / m³ based on the weight of the solids in the coating film. 2 The coating should be applied within the specified range. If the amount of tackifying coating applied is less than the specified range, it may not be possible for the tackifying coating to adhere to the substrate, compared to the case where the amount of tackifying coating applied is within the specified range. On the other hand, if the amount of tackifying coating applied is more than the specified range, the economic efficiency will decrease.

[0127] The composition for forming a tackifying coating applied to a substrate depends on the composition and coating amount used, but the solvent in the composition is removed by drying at a temperature of 80–150°C for 1–60 seconds. Therefore, even if the substrate is made of a low-melting-point plastic such as polypropylene, it will not be affected, and a tackifying coating can be formed economically.

[0128] Next, a gas barrier coating composition is applied onto the tackifying coating composition, which has been desolventized and is in a dry state. The coating amount of the gas barrier coating composition is determined based on the content of metal oxides, phosphate compounds, and metal alkoxides in the composition, and cannot be specified in general terms. It is preferably 0.05 to 3.0 g / m³ based on the weight of the solid content of the coating film. 2 A particularly preferred formulation has a solid content of 0.1–2.5 g / m³ based on the weight of the solids in the coating film. 2 The coating should be applied within the specified range. If the coating amount is less than the specified range, sufficient barrier properties cannot be obtained. On the other hand, even if the coating amount is more than the specified range, it is only less economical and does not offer any particular advantage.

[0129] In the coating composition for forming a gas barrier film of the present invention, although the composition and coating amount of the metal oxides, phosphate compounds, and metal alkoxides in the composition used also depend on the specific conditions, the gas barrier layer can be formed by heating at a temperature of 80–220°C, preferably 140–220°C, for 1 second to 10 minutes. This reduces the difference in shrinkage caused by heating the gas barrier layer and the tackifying coating, improves the crack resistance of the gas barrier layer, and significantly enhances the interlayer adhesion between the gas barrier layer and the tackifying coating, preventing the gas barrier layer from peeling off from the substrate even after sterilization processes such as boiling. Furthermore, compared to conventional gas barrier layers, a coating film can be formed efficiently at low temperatures and in a short time.

[0130] The application, drying, or heat treatment of the tackifying coating composition and the gas barrier coating composition can be carried out by conventionally known methods.

[0131] The coating method is not limited to this; for example, it can be applied by spraying, dipping, or by a doctor blade coater, roller coater, gravure coater, etc.

[0132] In addition, drying or heating treatment can be carried out through oven drying (heating), infrared heating, high frequency heating, vacuum drying, superheated steam, etc.

[0133] [Composition for forming adhesion-promoting coating layer]

[0134] As a composition for forming an tackifying coating that is applied to the surface of a substrate as needed, as described above, it is preferable to use: a conventionally known composition for forming an tackifying coating formed from a polyurethane resin, which is composed of a hydroxyl-containing compound that is the main agent of an acrylic resin, a polyol, etc., and an isocyanate-based curing agent; or a composition for forming an tackifying coating that further contains a silane coupling agent or a resin containing a hydrophilic group and a silane coupling agent.

[0135] <Polyurethane-based resin>

[0136] As the polyurethane resin constituting the tackifying coating, the following polyurethane resins, which are known to be used as tackifying coatings in the past, can be used, which include hydroxyl-containing compounds and isocyanate compounds that serve as the main agents of acrylic resins, polyols, etc.

[0137] In this invention, it is ideal to use a polyurethane resin with a glass transition temperature (Tg) of 80°C or higher, particularly in the range of 80 to 120°C. When the glass transition temperature is below this range, the heat resistance of the tackifying coating deteriorates compared to when it is within this range, and during the drying of the gas barrier layer, cracks may form in the gas barrier layer due to shrinkage caused by heating, resulting in reduced barrier properties.

[0138] As an acrylic resin, polymers and copolymers synthesized by solution polymerization or suspension polymerization using free radical initiators and the like can be used.

[0139] The glass transition temperature of the acrylic resin is preferably -50 to 100°C, more preferably 40 to 100°C. Furthermore, the number-average molecular weight of the acrylic resin is preferably 500,000 to 100,000, more preferably 500,000 to 80,000. Additionally, the hydroxyl value of the acrylic resin is preferably 10 to 200 mg KOH / g, more preferably 80 to 180 mg KOH / g.

[0140] There are no particular limitations on the monomers used for copolymer formation; copolymers composed of methyl acrylate, ethyl acrylate, methyl methacrylate, ethyl methacrylate, acrylic acid, methacrylic acid, itaconic acid, maleic acid, 2-hydroxyethyl methacrylate, tert-butyl acrylate, etc., can be used as needed.

[0141] Examples of polyols include: diols, polyester polyols, polyether polyols, acrylic polyols, or their urethane-modified forms, with acrylic polyols and diols being particularly preferred.

[0142] The glass transition temperature of the polyester polyol is preferably -50 to 100°C, more preferably -20°C to 80°C. Furthermore, the number-average molecular weight of these polyester polyols is preferably 500,000 to 100,000, more preferably 500,000 to 80,000.

[0143] Examples of diols include ethylene glycol, propylene glycol, diethylene glycol, butanediol, neopentyl glycol, and 1,6-hexanediol.

[0144] As a curing agent for polyurethane resins, i.e., isocyanate, aromatic diisocyanates, aromatic aliphatic diisocyanates, alicyclic diisocyanates, aliphatic diisocyanates, etc. can be used.

[0145] Examples of aromatic diisocyanates include, for example: toluene diisocyanate (2,4- or 2,6-toluene diisocyanate or mixtures thereof) (TDI); phenyl diisocyanate (m- or p-phenyl diisocyanate or mixtures thereof); 4,4'-diphenyl diisocyanate; 1,5-naphthalene diisocyanate (NDI); diphenylmethane diisocyanate (4,4'-, 2,4'-, or 2,2'-diphenylmethane diisocyanate or mixtures thereof) (MDI); 4,4'-xylene diisocyanate (TODI); 4,4'-diphenyl ether diisocyanate, etc.

[0146] Examples of aromatic aliphatic diisocyanates include, for example, phenyl diisocyanate (1,3- or 1,4-phenyl diisocyanate or mixtures thereof) (XDI), tetramethyl phenyl diisocyanate (1,3- or 1,4-tetramethyl phenyl diisocyanate or mixtures thereof) (TMXDI), ω,ω'-diisocyanate-1,4-diethylbenzene, etc.

[0147] Examples of alicyclic diisocyanates include: 1,3-cyclopentene diisocyanate, cyclohexane diisocyanate (1,4-cyclohexane diisocyanate, 1,3-cyclohexane diisocyanate), 3-isocyanate methyl-3,5,5-trimethylcyclohexyl isocyanate (isophorone diisocyanate, IPDI), methylene bis(cyclohexyl isocyanate) (4,4'-, 2,4'- or 2,2'-methylene bis(cyclohexyl isocyanate)) (hydrogenated MDI), methylcyclohexane diisocyanate (methyl-2,4-cyclohexane diisocyanate, methyl-2,6-cyclohexane diisocyanate), bis(isocyanate methyl)cyclohexane (1,3- or 1,4-bis(isocyanate methyl)cyclohexane or mixtures thereof) (hydrogenated XDI), etc.

[0148] Examples of aliphatic diisocyanates include, for example: trimethylene diisocyanate, 1,2-propylidene diisocyanate, butylidene diisocyanate (tetramethylene diisocyanate, 1,2-butylidene diisocyanate, 2,3-butylidene diisocyanate, 1,3-butylidene diisocyanate), hexamethylene diisocyanate, pentamethylene diisocyanate, 2,4,4- or 2,2,4-trimethylhexamethylene diisocyanate, and methyl caffeate 2,6-diisocyanate.

[0149] Polyisocyanate components can also be polyfunctional polyisocyanate compounds derived from the above-mentioned polyisocyanate monomers, such as isocyanurates, biurets, and urethanes, or polyfunctional polyisocyanate compounds containing terminal isocyanate groups obtained by reacting with polyols containing trimethylolpropane, glycerol, or other trifunctional or higher polyols.

[0150] The polyisocyanate component preferably has a glass transition temperature (Tg) of 50°C or higher and a number-average molecular weight (Mn) of 400 or higher, and particularly preferably has a glass transition temperature (Tg) of 60°C or higher and a number-average molecular weight (Mn) of 500 or higher.

[0151] In this invention, phenylenediamine diisocyanate is also preferably used among the isocyanate components.

[0152] <Resin containing hydrophilic group>

[0153] The resin containing hydrophilic groups is not limited to this, and examples include water-dispersible or water-soluble polyester resins, water-dispersible or water-soluble acrylic resins, and water-dispersible or water-soluble polyurethane resins. In this invention, polyester resins are preferred, and carboxyl-containing polyester resins are more preferably used.

[0154] Carboxyl-containing polyester resins can be prepared by combining carboxylic anhydrides such as phthalic anhydride, succinic anhydride, maleic anhydride, trimellitic anhydride, itaconic anhydride, and citraconic anhydride with monomer components commonly used in the polymerization of polyester resins.

[0155] Regarding the monomeric components, examples of polycarboxylic acid components include: aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, phthalic acid, and naphthalene dicarboxylic acid; aliphatic dicarboxylic acids such as succinic acid, glutaric acid, adipic acid, azelaic acid, sebacic acid, dodecanoic acid, and dimer acids; unsaturated dicarboxylic acids such as maleic acid (anhydride), fumaric acid, and terpene-maleic acid adducts; alicyclic dicarboxylic acids such as 1,4-cyclohexanedicarboxylic acid, tetrahydrophthalic acid, hexahydroisophthalic acid, and 1,2-cyclohexenedicarboxylic acid; and trivalent or higher polycarboxylic acids such as trimellitic acid (anhydride), pyromellitic acid (anhydride), and methylcyclohexenetricarboxylic acid. One or more of these can be selected. In this invention, from the viewpoint of heat resistance, the proportion of aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, and naphthalene dicarboxylic acid in the polycarboxylic acid components constituting the polyester resin is preferably 50 mol% or more.

[0156] Furthermore, there are no particular limitations on the polyol components constituting the polyester resin; one or more of the following substances may be used, or a combination of two or more: ethylene glycol, propylene glycol (1,2-propanediol), 1,3-propanediol, 1,4-butanediol, 1,2-butanediol, 1,3-butanediol, 2-methyl-1,3-propanediol, neopentyl glycol, 1,5-pentanediol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, 2-ethyl-2-butyl-1,3-propanediol, 2,4-dimethyl-1,5-pentanediol, 1-methyl-1, Aliphatic diols such as 8-octanediol, 3-methyl-1,6-hexanediol, 4-methyl-1,7-heptanediol, 4-methyl-1,8-octanediol, 4-propyl-1,8-octanediol, and 1,9-nonanediol; ether alcohols such as diethylene glycol, triethylene glycol, polyethylene glycol, polypropylene glycol, and polytetramethylene glycol; alicyclic polyols such as 1,4-cyclohexanediol, 1,3-cyclohexanediol, 1,2-cyclohexanediol, tricyclodecanediols, and hydrogenated bisphenols; and polyols with three or more tertiary groups such as trimethylolpropane, trimethylolethane, and pentaerythritol. In this invention, ethylene glycol, propylene glycol, and neopentyl glycol may be appropriately used among the above-mentioned polyol components.

[0157] Carboxyl-containing polyester resins can be manufactured by the following known methods: polycondensation of one or more of the above-mentioned polycarboxylic acid components and one or more of the polyol components; followed by depolymerization of the polycarboxylic acid components, such as terephthalic acid, isophthalic acid, trimellitic anhydride, trimellitic acid, benzopyrene, etc.; furthermore, ring-opening addition of acid anhydrides, such as phthalic anhydride, maleic anhydride, trimellitic anhydride, ethylene glycol bis(triptyl) dianhydride, etc., after polycondensation.

[0158] The acid value of the carboxyl-containing polyester resin is preferably 1-80 KOH mg / g, particularly preferably 10-30 KOH mg / g, and the glass transition temperature (Tg) is preferably 0-120℃, particularly preferably in the range of 67-80℃.

[0159] The carboxyl-containing polyester resin used can be a mixed polyester resin as long as the acid value and Tg of the mixture are within the above range.

[0160] Furthermore, the carboxyl-containing polyester resin is preferably an amorphous polyester.

[0161] <Silane coupling agent>

[0162] Epoxy-based silane coupling agents are preferred as silane coupling agents used in tackifying coatings.

[0163] As such epoxy silane coupling agents, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-epoxypropoxypropylmethyldimethoxysilane, 3-epoxypropoxypropylmethyldiethoxysilane, 3-epoxypropoxypropyltriethoxysilane, 3-epoxypropoxypropyltriethoxysilane, and 3-epoxypropoxypropyltrimethoxysilane can be used.

[0164] Other examples of silane coupling agents include tetramethoxysilane, tetraethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, and 3-isocyanate-propyltriethoxysilane, which can be used as needed.

[0165] Furthermore, regarding the silane coupling agents used, for the purpose of improving hot water resistance and sealing, silane coupling agents that have undergone hydrolysis or condensation reaction with silane coupling agents as needed can be used.

[0166] The composition for forming the tackifying coating can be any of the aqueous or solvent-based types. From the point of view of the working environment, it is ideal to use an aqueous composition.

[0167] When using the above-mentioned polyurethane resin, the composition for forming the tackifying coating preferably also contains an epoxy silane coupling agent. Furthermore, the polyurethane resin used is preferably a water-soluble or water-dispersible polyurethane.

[0168] On the other hand, when the above-mentioned resin containing hydrophilic groups is used in the composition for forming tackifying coatings, it is preferable to prepare the composition containing carboxyl-containing polyester resin and epoxy silane coupling agent.

[0169] Regarding epoxy-based silane coupling agents, they are preferably contained in an amount of 1 to 80 parts by weight relative to 100 parts by weight of the solid component of the polyurethane resin. On the other hand, they are preferably contained in an amount of 100 to 400 parts by weight, and particularly preferably 150 to 300 parts by weight, relative to 100 parts by weight of the solid component of the carboxyl-containing polyester resin.

[0170] When the amount of epoxy silane coupling agent is less than the range mentioned above, satisfactory crack resistance during drying cannot be obtained compared to when it is within the range. On the other hand, even if the amount of epoxy silane coupling agent exceeds the range mentioned above, it is difficult to further improve the adhesion and crack resistance, and it may even impair the hot water resistance, thus deteriorating from an economic point of view.

[0171] In addition, as an aqueous medium, it may contain the same previously known aqueous medium used in the composition for forming the barrier layer, as well as organic solvents such as alcohols, polyols, and their derivatives.

[0172] In addition to the components mentioned above, the composition for forming tackifying coatings may also contain known curing accelerators, fillers, softeners, anti-aging agents, stabilizers, adhesion promoters, leveling agents, defoamers, plasticizers, inorganic fillers, tackifying resins, fibers, pigments and other colorants, and usable time extenders.

[0173] Examples

[0174] The present invention will be further illustrated by the following embodiments, but the present invention is not limited to the following examples. It should be noted that the various measurement and evaluation methods of the embodiments and comparative examples are described below.

[0175] (Example 1)

[0176] [Preparation of coating composition for forming gas barrier coating film]

[0177] As a coating composition for forming a barrier coating film (hereinafter referred to as "barrier coating"), zirconium oxide sol (manufactured by Daiichi Rare Element Chemical Industry Co., Ltd., zirconium oxide sol ZSL-00120B (crystalline zirconium oxide, tetragonal crystal system, solid content (converted to ZrO2) = 20%) is used as the metal oxide. First, the zirconium oxide sol is prepared using water and isopropanol solvents in a manner with a solid content of 5-7% and a water / isopropanol ratio of 60 / 40. Next, relative to 100 parts by mass of the solid content of the zirconium oxide sol, 44.7 parts by mass of aluminum isopropoxide (manufactured by Wako Pure Chemical Co., Ltd.) as an additive and 53.5 parts by mass of phosphoric acid (manufactured by Wako Pure Chemical Co., Ltd., concentration = 75%) as a phosphoric acid compound are added, and the mixture is dispersed in a homogenizer for a specified time to obtain the barrier coating.

[0178] [Method for producing gas barrier laminate]

[0179] The gas-barrier laminate was prepared using the prepared barrier coating material as follows: On a 25 μm thick biaxially stretched polyester film (manufactured by Toyobo Co., Ltd., E5102) substrate, a doctor blade coater was used to coat it at a rate of 1.8–2.2 g / m². 2 The above-mentioned barrier coating is applied in the manner described above, and then dried in a box oven at 200°C for 2 minutes to obtain a gas barrier laminate.

[0180] [Method for preparing sample for evaluation of gas barrier property and the like]

[0181] For the samples used to evaluate gas barrier properties (hereinafter referred to as "evaluation samples"), the barrier coating surface of the aforementioned gas barrier laminate was coated using a doctor blade coater at a coating amount of 4.0 g / m². 2 A sample for evaluating gas barrier properties was prepared by coating a polyurethane adhesive (manufactured by Mitsui Chemicals Co., Ltd., TAKENATE A-315 / TAKENATE A-50), drying it in a dryer, and then laminating the 25μm thick biaxially stretched polyester film.

[0182] (Example 2)

[0183] In Example 1, relative to 100 parts by mass of the solid component of zirconium oxide sol, 47.0 parts by mass of aluminum isopropoxide (manufactured by Wako Pure Chemical Industries, Ltd.) as an additive and 56.1 parts by mass of phosphoric acid (manufactured by Wako Pure Chemical Industries, Ltd., concentration = 75%) as a phosphoric acid compound were added, based on the non-volatile component of phosphoric acid. Otherwise, a gas barrier laminate and an evaluation sample were obtained by the same method as in Example 1.

[0184] (Example 3)

[0185] In Example 1, relative to 100 parts by mass of the solid component of zirconium oxide sol, 53.7 parts by mass of aluminum isopropoxide (manufactured by Wako Pure Chemical Industries, Ltd.) as an additive and 64.2 parts by mass of phosphoric acid (manufactured by Wako Pure Chemical Industries, Ltd., concentration = 75%) as a phosphoric acid compound were added, based on the non-volatile component of phosphoric acid. Otherwise, a gas barrier laminate and an evaluation sample were obtained by the same method as in Example 1.

[0186] (Example 4)

[0187] In Example 1, relative to 100 parts by mass of the solid component of zirconium oxide sol, 58.1 parts by mass of aluminum isopropoxide (manufactured by Wako Pure Chemical Co., Ltd.) as an additive and 69.5 parts by mass of phosphoric acid (manufactured by Wako Pure Chemical Co., Ltd., concentration = 75%) as a phosphoric acid compound were added, based on the non-volatile component of phosphoric acid. Otherwise, a gas barrier laminate and an evaluation sample were obtained by the same method as in Example 1.

[0188] (Example 5)

[0189] In Example 1, 67.1 parts by mass of aluminum isopropoxide (manufactured by Wako Pure Chemical Industries, Ltd.) as an additive and 80.2 parts by mass of phosphoric acid (manufactured by Wako Pure Chemical Industries, Ltd., concentration = 75%) as a phosphoric acid compound were added relative to 100 parts by mass of the solid component of the zirconium oxide sol, based on the non-volatile component of the phosphoric acid. Otherwise, a gas barrier laminate and an evaluation sample were obtained by the same method as in Example 1.

[0190] (Example 6)

[0191] In Example 1, relative to 100 parts by mass of the solid component of zirconium oxide sol, 71.5 parts by mass of aluminum isopropoxide (manufactured by Wako Pure Chemical Co., Ltd.) as an additive and 85.5 parts by mass of phosphoric acid (manufactured by Wako Pure Chemical Co., Ltd., concentration = 75%) as a phosphoric acid compound were added, based on the non-volatile component of phosphoric acid. Otherwise, a gas barrier laminate and an evaluation sample were obtained by the same method as in Example 1.

[0192] (Example 7)

[0193] In Example 1, relative to 100 parts by mass of the solid component of zirconium oxide sol, 76.0 parts by mass of aluminum isopropoxide (manufactured by Wako Pure Chemical Industries, Ltd.) as an additive and 90.9 parts by mass of phosphoric acid (manufactured by Wako Pure Chemical Industries, Ltd., concentration = 75%) as a phosphoric acid compound were added, based on the non-volatile component of phosphoric acid. Otherwise, a gas barrier laminate and an evaluation sample were obtained by the same method as in Example 1.

[0194] (Example 8)

[0195] In Example 1, 8.5 parts by mass of aluminum hydroxide (manufactured by Wako Pure Chemical Industries, Ltd.) as an additive and 53.5 parts by mass of phosphoric acid (manufactured by Wako Pure Chemical Industries, Ltd., concentration = 75%) as a phosphoric acid compound were added relative to 100 parts by mass of the solid component of zirconium oxide sol, based on the non-volatile component of phosphoric acid. Otherwise, a gas barrier laminate and an evaluation sample were obtained by the same method as in Example 1.

[0196] (Comparative Example 1)

[0197] In Example 1, relative to 100 parts by mass of the solid component of zirconium oxide sol, 40.3 parts by mass of aluminum isopropoxide (manufactured by Wako Pure Chemical Industries, Ltd.) as an additive and 48.1 parts by mass of phosphoric acid (manufactured by Wako Pure Chemical Industries, Ltd., concentration = 75%) as a phosphoric acid compound were added, based on the non-volatile component of phosphoric acid. Otherwise, a gas barrier laminate and an evaluation sample were obtained by the same method as in Example 1.

[0198] (Comparative Example 2)

[0199] In Example 1, a dispersion process using rotating blades was performed for a specified time. Otherwise, a gas barrier laminate and an evaluation sample were obtained by the same method as in Example 1.

[0200] (Comparative Example 3)

[0201] In Example 1, 80.5 parts by mass of aluminum isopropoxide (manufactured by Wako Pure Chemical Industries, Ltd.) as an additive and 96.2 parts by mass of phosphoric acid (manufactured by Wako Pure Chemical Industries, Ltd., concentration = 75%) as a phosphoric acid compound were added relative to 100 parts by mass of the solid component of the zirconium oxide sol, based on the non-volatile component of the phosphoric acid. Otherwise, a gas barrier laminate and an evaluation sample were obtained by the same method as in Example 1.

[0202] (Evaluation method)

[0203] The following evaluation methods were used, as shown in Tables 1 and 2, to obtain the evaluation results of the gas barrier laminate and the evaluation samples.

[0204] [Oxygen transmission rate]

[0205] The evaluation samples obtained in the examples and comparative examples were measured using an oxygen permeability measuring device (Modern Control, OX-TRAN 2 / 21). The measurement conditions were set at a temperature of 40°C and a relative humidity of 90%.

[0206] [Water vapor transmission rate]

[0207] The vapor barrier properties of the samples obtained in the examples and comparative examples were measured using a water vapor transmission rate measuring device (Modern Control PERMATRAN-W3 / 34, Technolox Deltaperm-UH, and Sempa HiBarSens2.0). The measurement conditions were set at a temperature of 40°C and a relative humidity of 90%.

[0208] [Infrared absorption spectrum]

[0209] Regarding the gas barrier laminates obtained in the examples and comparative examples, the infrared absorption spectra of the gas barrier coatings coated on the polyester substrates were measured using a Fourier transform infrared spectrophotometer (Japan Spectrophotometer Co., Ltd., FT / IR-6600).

[0210] <Measurement conditions for FT-IR apparatus>

[0211] Instrument used: JASCO FT / IR-6600.

[0212] Measurement conditions: Method ATR (Ge prism).

[0213] Detector MCT.

[0214] Thunder Dome expansion kit.

[0215] Wavenumber range 800–4000 cm -1 .

[0216] Membrane measurement surface is a barrier coating surface.

[0217] [Optical properties]

[0218] Regarding the gas barrier laminates obtained in the examples and comparative examples, the detector side for measuring the gas barrier laminate was used as the polyester film substrate side, and the total light transmittance (%), haze (%), and gloss were measured using a haze meter (NDH8000 manufactured by Nippon Denshoku Kogyo Co., Ltd.) and a gloss meter (VG8000 manufactured by Nippon Denshoku Kogyo Co., Ltd.).

[0219] [X-ray fluorescence evaluation]

[0220] As a method for evaluating the elements contained in each gas barrier laminate obtained in the examples and comparative examples, phosphorus, aluminum, and zirconium can be quantified using a commercially available fluorescence X-ray analysis device. The layer strength obtained in the determination of each gas barrier laminate is set as P / Zr for P and Zr, and Al / Zr for Al and Zr, and the content ratio of each element in the coating film is calculated and used for evaluation.

[0221] <Measurement conditions for X-ray fluorescence analyzer>

[0222] Instrument used: Rigaku Corporation ZSX PrimusII.

[0223] Measurement conditions: The object of measurement contains P-Kα rays and Al-Kα rays.

[0224] Zr-Kα rays.

[0225] The diameter was measured to be 10 mm.

[0226] X-ray Rh (4.0 kW) was measured.

[0227] The film measurement is performed by shining X-rays into the barrier coating from the side of the film.

[0228] [Viscosity]

[0229] The viscosity of each barrier coating obtained in the examples and comparative examples was determined using a Type B viscometer (manufactured by EKO Seiki Co., Ltd., Brookfield DV2T). The measurement conditions were set as follows: temperature 25°C, spindle SC4-18, chamber 13R, and rotation speeds of 50 rpm and 200 rpm.

[0230] The various measurement and evaluation results of the above-described embodiments and comparative examples are shown in Tables 1 and 2.

[0231] [Table 1]

[0232]

[0233] [Table 2]

[0234]

[0235] [Abbreviations in Tables 1 and 2]

[0236] NV: Solid component of metal oxide in metal oxide sol; ZSL-00120B: Crystalline zirconium oxide; TT: Total transmittance; Hz: Haze; Gs (60°): Gloss at an angle of 60°; P / Zr: Ratio of phosphorus (P) derived from phosphate compounds to zirconium (Zr) in the gas barrier laminate; Al / Zr: Ratio of aluminum (Al) derived from additives to zirconium (Zr) in the gas barrier laminate.

[0237] Industrial Applicability

[0238] The coating composition for forming a gas barrier coating of the present invention can form a coating with excellent oxygen barrier and water vapor barrier properties, and can be preferably used as a transparent high-barrier packaging material.

[0239] Furthermore, it has particularly excellent water vapor barrier properties, so its applications as a gas barrier laminate are not limited to this. It can also be used in food packaging containers, packaging materials for retort applications, pharmaceutical packaging materials, substrates for vapor deposition, electronic equipment, circuit board materials, semiconductor materials, solar cell components, organic EL light-emitting element components, organic EL lighting components, electronic paper, battery casings, etc.

[0240] Description of Reference Signs in the Drawings

[0241] 1: Substrate; 2: Tackifying coating; 3: Gas barrier layer; 4: Adhesive layer; 5: Resin layer.

Claims

1. A gas-barrier laminate, characterized in that, It is a gas barrier laminate with a gas barrier coating on a substrate, wherein, The coating is formed from reaction products obtained by reacting at least one of a metal alkoxide, a hydrolysate of a metal alkoxide, a metal hydroxide, a zirconium oxide, and a phosphoric acid compound or a sulfuric acid compound. The content ratio of Zr (Zr-Kα) to P (P-Kα) in the fluorescence X-ray determination of the coating film is in the range of 1.39 to 2.

59. In the infrared absorption spectrum of the coating film, 2600–3700 cm⁻¹ -1 The peak area P2 is 850–1350 cm⁻¹ -1 The ratio of the peak area P1 to P2 / P1 is less than 0.

772.

2. The gas-barrier laminate according to claim 1, wherein, A 25 μm thick biaxially stretched polyethylene terephthalate film was used as the substrate, and a coating with a thickness of 1.8–2.2 g / m was formed on the substrate. 2 The haze of the gas barrier laminate of the coating is less than 9.0%.

3. The gas barrier laminate according to claim 1 or 2, wherein, The metal alkoxide, the hydrolysate of the metal alkoxide, and the metal hydroxide are all aluminum. The ratio of Zr (Zr-Kα) to Al (Al-Kα) in the fluorescence X-ray determination of the coating film is in the range of 0.15 to 0.

58.

4. The gas-barrier laminate according to claim 1 or 2, wherein, The coating film exhibits infrared absorption in the range of 1000–1120 cm⁻¹ -1 It exhibits infrared absorption within a certain range, resulting in the largest absorption peak.

5. The gas-barrier laminate according to claim 1 or 2, wherein, A 25 μm thick biaxially stretched polyethylene terephthalate film was used as the substrate, and the coating amount formed on the substrate was 1.8–2.2 g / m. 2 The gas barrier laminate, consisting of a 25 μm thick biaxially stretched polyethylene terephthalate film layered on top of the coating and an adhesive layer spaced between the coating, exhibits a water vapor permeability of less than 0.100 g / m³ at 40°C and 90% RH. 2 ·sky.

6. A substrate for vapor deposition, the substrate comprising a gas barrier laminate according to claim 1 or 2.

7. A coating composition for forming a gas barrier film, characterized in that, The coating composition for forming a barrier coating film is a coating composition for forming a barrier coating film containing at least one of a metal alkoxide, a hydrolysate of a metal alkoxide, a metal hydroxide, a metal oxide, and a phosphoric acid compound or a sulfuric acid compound. When the coating composition for forming a barrier coating film is prepared into a dispersion with a solid content of 5-7% by mass and a water / isopropanol ratio of 60 / 40, the viscosity ratio A / B of the dispersion, measured using a Brookfield viscometer at a temperature of 25°C and a spindle speed of 50 rpm, is less than 3.

6.

8. The coating composition for forming a barrier coating film according to claim 7, wherein, When a coating composition for forming a barrier coating film is prepared into a dispersion with a solid content of 5-7% by mass and a water / isopropanol ratio of 60 / 40, the viscosity of the dispersion, measured using a Brookfield viscometer at a temperature of 25°C and a spindle speed of 50 rpm, is less than 113.9 mPa·sec.

9. The coating composition for forming a barrier coating film according to claim 7 or 8, wherein, The metal alkoxide or metal hydroxide is at least one of aluminum, titanium, iron, and zirconium.

10. The coating composition for forming a barrier coating film according to claim 7 or 8, wherein, The metal alkoxide is at least one of methanol, ethanol, propoxide, isopropoxide, butoxide, isobutoxide, sec-butoxide, and tert-butoxide.

11. The coating composition for forming a barrier coating film according to claim 7 or 8, wherein, The metal alkoxide is aluminum isopropoxide.

12. The coating composition for forming a barrier coating film according to claim 7 or 8, wherein, The metal hydroxide is aluminum hydroxide.

13. The coating composition for forming a barrier coating film according to claim 7 or 8, wherein, The metal oxide is zirconium oxide or aluminum oxide.

14. The coating composition for forming a barrier coating film according to claim 7 or 8, wherein, The metal oxide is crystalline zirconium oxide.

15. The coating composition for forming a barrier coating film according to claim 7 or 8, wherein, The phosphoric acid compound is at least one of orthophosphoric acid, metaphosphoric acid, polyphosphoric acid, and cyclic polyphosphoric acid.

16. A method for manufacturing a coating composition for forming a gas barrier film, characterized in that, The method for manufacturing the coating composition for forming a barrier coating film according to claim 7 is wherein at least one of a metal alkoxide, a hydrolysate of a metal alkoxide, a metal hydroxide, a metal oxide, and a phosphoric acid compound or a sulfuric acid compound is mixed, and the resulting mixture is stirred such that the viscosity, measured using a Brookfield viscometer at a temperature of 25°C and a spindle speed of 50 rpm, is less than 113.9 mPa·sec.

Citation Information

Patent Citations

  • JP1974061054A

  • Gas-barrier coating composition and gas-barrier laminate

    WO2022075352A1